PENGARUH MODEL PEMBELAJARAN NHT BERBANTUAN MEDIA KOTAK PUZZEL TERHADAP HASIL BELAJAR SISWA PADA PELAJARAN IPA - Mina Kussaniah; Indiati Indiati; Putri Meinita Triana (Khazanah Pendidikan, 2021)
This study aimed to examine influence of NHT learning model using box puzzle media toward student learning outcomes on IPA subjects class IV SD Muhammadiyah Jetis Salaman Magelang.The research design was quasy experimental design with one group pretest posttest model. The research variable was IPA learning outcomes. Data analysis used was parametric statistical techniques paired sampel t-test. The research subject were 15 students class IV SD Muhammadiyah Jetis Salaman Magelang. The data collection methods used test questions. The results of this study indicated that NHT learning model using box puzzle media effective to increased student learning outcomes on IPA subjects class IV SD Muhammadiyah Jetis Salaman Magelang. The increase student learning outcomes was evidenced by the result of test analysis paired sampel t-test with the probability of the sign value (2-tailed) 0,000 < 0,005, that mean was significant difference between before and after being given treatment with HT learning model using box puzzle media. Based on the research results, it was concluded that the application of NHT learning model using box puzzle media influenced to student learning outcomes on IPA subjects Keyword: NHT learning model using box puzzle media, learning outcomes